From solitary to an adaptive continuum process: Toward a new framework of natural disaster emergency decision-making - Siska Sasmita; Bevaola Kusumasari; Agus Pramusinto; Ely Susanto (Indonesian Journal of Geography, 2022)
Major studies in emergency decisions are focusing on how techno-rational approaches applied in early warning systems to produce an output; rarely explore its opponent, the naturalistic intervention, or how both paradigms function in a crisis decision process. This research aims to identify the actual process of emergency decision making in the context of natural hazard studies, whether it employs the techno-rational or purely naturalistic approach. A systematic review is adopted to assess papers in the period 2000-2018 within the ‘emergency decision making’ AND “natural disaster” keywords. Research finds a non-techno-rational paradigm that contributes to producing a decision outcome. Instead of categorizing it the naturalistic paradigm as named by the scholars, we labelled it a non-technological paradigm. It consists of two main instruments: individual and institutional interventions, that together with the techno-rational instrument develop an adaptive continuum behavior while operating in uncertainty condition in order to generate an effective evacuation order for vulnerable people.